Wolves in the Amazon? Child perceptions of a distant natural environment in an English primary school. Issue 2 (5th May 2021) - Rey-Goyeneche, Jennifer A.; Alexander, Patrick
Abstract: By analysing an academic exhibition on the Amazon region made by Year 5 children from an Oxford-based primary school, this qualitative study explores the ways that children perceive a representation of a natural environment geographically distant from their home context. The phenomenographic analysis of written and visual documentary sources focuses on incorporated biophysical and socio-cultural elements. Three hierarchically inclusive ways of perceiving the Amazon were identified: (1) Nature as species of wild fauna and their habitat; (2) Nature as political economy; and (3) Nature as an imaginative world. Correspondingly, findings highlighted: (1) children's affiliation to other living organisms; (2) children's stereotypical constructs in relation to developing countries; and (3) nature as a concept that is actively constructed by children, including the conjuring of imagined 'natural' worlds. The findings have implications for interdisciplinary approaches to Environmental Education in primary contexts.